Financing "A sustainable food future" - Díaz-Bonilla, Eugenio; Loboguerrero, Ana Maria; Verchot, Louis; Viglizzo, Ernesto; Mirzabaev, Alisher (T20 Argentina, 2018)
Achieving a “sustainable food future” requires building food systems that, in line with the related Sustainable Development Goals (SDGs), support growth and employment, ensure social inclusiveness and equity, promote climate resilience and environmental sustainability, protect biodiversity, and generate healthy diets for all. Many policy, institutional, technological and investment innovations are needed to build such food systems. This brief considers as a necessary foundation, the existence and continuous development of adequate technologies and innovations, including the ones related to soils, land, water, ecosystems, and, in general, those that have been called Climate Smart Agriculture (CSA) or Climate-friendly Sustainable Agriculture (CFSA). The main question this policy brief focuses on is how to mobilize the financial resources to support investments in those technologies and sustainable food systems at the scale needed to have some meaningful global impact. It suggests that a project preparation and financial structuring facility of appropriate scale would help leverage scarce public-sector funds to mobilize the much larger pool of private financial funds that may be interested in participating in these investments but now lack adequately structured projects and investment vehicles to that effect. The policy brief argues that this proposal is similar in spirit to the approach for investments in sustainable infrastructure presented by the Argentinean Presidency.